Study of markers of inflammation as predictors and prognosticators of acute coronary syndrome in patients with acute chest pain (Health Renaissance, 2015)
Background: The role of inflammation in the pathogenesis of acute coronary  syndrome (ACS) is established, however use of inflammatory markers as predictors  for future short-term cardiovascular events in patients of acute coronary syndrome.  Objective: To assess whether inflammatory markers C-reactive protein (hs-CRP),  total leucocyte count (TLC) and serum albumin can correlate with the diagnosis  of ACS in patients with acute chest pain and to see whether these markers can be  used to predict short-term cardiovascular events in patients of ACS. Methods: All  Patients presenting within 12 hours of the onset of central non traumatic chest pain  were enrolled and investigated, the diagnosis of ACS was made as per JACC 2004  guidelines for ST-elevation myocardial infarction, unstable angina and non-ST  elevation myocardial infarction. All patients received routine institutional care and  treatment as per diagnosis blinded to CRP, albumin, and total leucocyte count (TLC).  The independent predictors of ACS and predictors of adverse events in 30 days was  evaluated using multivariate analysis. Results: one forty nine patients of ≥ 18 years  (88 male, 61 female) which were included in the study, the diagnosis of non-ischemic  chest pain (NICP)were in 30 (20%) and ACS in 119 (80%) patients. TLC and hs-CRP levels were higher (11576±3083, 14.04±6.17) in patients with ACS compared  to NICP (5596±1370, 2.39±1.55) with significant P-value (